Association between BMI, Immunocompromised Status, and Pulmonary TB History with Severity of TB Spondylitis - Mulia, Maulidia; Supartono, Basuki; Yulianti, Retno; Amalia, Muttia (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2025)
Abstract Background: Tuberculous spondylitis is the most common form of skeletal TB that can cause joint damage and disability if left untreated. Several studies have discussed risk factors associated with the severity of TB spondylitis. However, there are differences in findings among these studies, especially regarding age, sex, body mass index, immunocompromised conditions, and pulmonary TB history. Early detection through risk factor screening and adequate treatment can be useful to prevent disease severity. Objective: This research aims to find out the association between risk factors and the severity of TB spondylitis using GATA classification. Methods: Observational analytical methods with a retrospective hospital-based cross-sectional study design were used. Using consecutive sampling technique. The total research sample was 50 patients diagnosed with TB spondylitis between January 1, 2022-December 31, 2024 at Gatot Soebroto Army Hospital Jakarta. Result: The characteristics of TB spondylitis patients were mostly adults (68%), male (54%), had normal BMI (42%), had immunocompromised conditions (52%), and had a history of pulmonary TB (58%), with severe TB spondylitis (42%). Bivariate analysis showed a significant association between BMI (p=0.033) and immunocompromised conditions (p=0.047) and no significant association between age (p=0.482), sex (p=0.356), and history of pulmonary TB (p=0.469) with the severity of TB spondylitis. Conclusion: A significant association was found between BMI and immunocompromised conditions with the severity of TB spondylitis. However, there is no significant association between pulmonary TB history with the severity of TB spondylitis.Keywords: risk factors, tuberculous spondylitis, severity